Upscaling local domains in regional domains: An offline nudging approach. (March 2023) - Sobrinho, João; de Pablo, Hilda; Pinto, Lígia; Neves, Ramiro
Abstract: In ocean modelling systems, transfer of information is typically from regional domain (RD) to local domain (LD – one-way) and, where there is an advantage in upscaling the LD into the RD (two-way), both domains are run at the same time transferring information online, resulting in two-way nesting systems. This article develops an offline (relaxation-based) upscaling approach, enabling the upscaling of several LDs simultaneously, run by different institutions or modelling tools at the same time as the RD is improved with the best available local knowledge. The approach is applied to the Tagus Region of Freshwater Influence, Portugal, where incremental upscaling simulations are tested, compared to the traditional downscaling approach, and validated against field data. Results show smoother solutions with upscaling, particularly at the boundaries between domains, where a less restricted estuarine plume significantly improved the surface salinity patterns at both sides of the boundary, during an extreme precipitation event. Highlights: An offline upscaling methodology is integrated in the MOHID modelling system. The algorithm considers nudging of velocity, temperature and salinity fields. Upscaling is done directly from output results into regional domains. The offline approach optimizes the upscaling in operational modelling.